Possible Effects of the Financial Crisis on Managers’ Attitudes to Older Workers - Solem, Per Erik (Nordic Journal of Working Life Studies, 2012)
The article explores the possible short-term effects of the financial crisis in Norway on cognitive, affective, and behavioral components of managers’ attitudes to older workers. The quick shifts in business cycles in 2008 and 2009, i.e., the financial crisis, produced some immediate reactions among managers. In particular, the protection of older workers by downsizing (the seniority principle) gained less support within the first half year of the crisis; however, there was a return to the former level of support within the next half year. This pattern of change was observed in the private sector, while managers in the public sector changed attitudes on a smaller scale and in the direction of increased support for the seniority principle. The data are from the Norwegian Senior Policy Barometer where national samples of managers in private companies and in the public sector are interviewed. The study has a time series design with new samples (N=750) each year from 2003 to 2011. The cognitive component of attitudes was less affected by the financial crisis than the behavioral disposition mentioned above. The tendency was for more positive conceptions of older workers among managers in the public sector. In the private sector, the views of managers changed even less and in the opposite direction. An impact of more gradual business cycles is seen in the affective component of attitudes. Yet, older workers are among the least popular categories to recruit in both rising and falling cycles. The finding that managers in the private sector are more affected than managers in the less market-exposed public sector supports the possible effects of the financial crisis on attitudes to older workers. For senior policy, it is notable to keep track of long-term trends and not to be beset by short-term shifts in the need for older workers. Lasting effects of falling business cycles on the employment of older workers may be prevented by reinforcing a solid basis of realistic cognitions about older workers and by openness concerning affective aspects of aging and older workers.